Rural family medicine as a career option among Hungarian medical students - András Mohos; Gergő József Szőllősi; László Róbert Kolozsvári; Jozsef Rinfel; Albert Varga; Maria Marko Kucsera; Csenge Hargittay; Peter Torzsa (European Journal of General Practice, 2023)
AbstractBackground The shortage of family physicians is a considerable challenge in Hungary. The number of vacant practices is increasing and the rural and deprived areas are more affected.Objectives This study aimed to investigate medical students’ attitudes towards rural family medicine.Methods The current study used a cross-sectional design with a self-administered questionnaire. Each of the four Hungarian medical universities was represented by their medical students from December 2019 to April 2020.Results The response rate was 67.3% (n = 465/691). Only 5% of the participants plan to be a family doctor, 5% of the students plan to work in rural areas. On a 5-point Likert scale (1 = ‘surely not’, 5 = ‘surely yes’), half of the participants answered 1 or 2 to choose rural medical work, while 17.5% answered 4 or 5. There was a significant relationship between rural working plans and rural origin (OR = 1.97; p = 0.024), and the plan to work in family practice (OR = 4.90; p < 0.001).Conclusion Family medicine is not a popular career option among Hungarian medical students and rural medical work is even less attractive. Medical students with a rural origin and an interest in family medicine are more likely to plan to work in rural areas. More objective information and experience need to be given to medical students about rural family medicine to increase the attractiveness of the speciality.